Haptoglobin genotype and outcome after aneurysmal subarachnoid haemorrhage. Issue 3 (14th January 2020) - Morton, Matthew J; Hostettler, Isabel C; Kazmi, Nabila; Alg, Varinder S; Bonner, Stephen; Brown, Martin M; Durnford, Andrew; Gaastra, Benjamin; Garland, Patrick; Grieve, Joan; Kitchen, Neil; Walsh, Daniel; et al.
Abstract : Objective: After aneurysmal subarachnoid haemorrhage (aSAH), extracellular haemoglobin (Hb) in the subarachnoid space is bound by haptoglobin, neutralising Hb toxicity and helping its clearance. Two exons in the HP gene (encoding haptoglobin) exhibit copy number variation (CNV), giving rise to HP1 and HP2 alleles, which influence haptoglobin expression level and possibly haptoglobin function. We hypothesised that the HP CNV associates with long-term outcome beyond the first year after aSAH. Methods: The HP CNV was typed using quantitative PCR in 1299 aSAH survivors in the Genetics and Observational Subarachnoid Haemorrhage (GOSH) Study, a retrospective multicentre cohort study with a median follow-up of 18 months. To investigate mediation of the HP CNV effect by haptoglobin expression level, as opposed to functional differences, we used rs2000999, a single nucleotide polymorphism associated with haptoglobin expression independent of the HP CNV. Outcome was assessed using modified Rankin and Glasgow Outcome Scores. SAH volume was dichotomised on the Fisher grade. Haemoglobin-haptoglobin complexes were measured in cerebrospinal fluid (CSF) of 44 patients with aSAH and related to the HP CNV. Results: The HP2 allele associated with a favourable long-term outcome after high-volume but not low-volume aSAH (multivariable logistic regression). However rs2000999 did not predict outcome. The HP2 allele associated with lower CSF haemoglobin-haptoglobin complex levels. The CSF Hb concentration after high-volume and low-volume aSAH was, respectively, higher and lower than the Hb-binding capacity of CSF haptoglobin. Conclusion: The HP2 allele carries a favourable long-term prognosis after high-volume aSAH. Haptoglobin and the Hb clearance pathway are therapeutic targets after aSAH.